2020
DOI: 10.1002/suco.201900577
|View full text |Cite
|
Sign up to set email alerts
|

Carbon emission analyses of concretes made with recycled materials considering CO2 uptake through carbonation absorption

Abstract: The effect of incorporation of recycled powder and CO2 absorption of concrete was not considered in the previous life cycle assessment studies. This study evaluated the carbon emission of recycled concrete with different replacement rate of recycled powder and recycled coarse aggregate, taking the carbon absorption in storage and service phase into consideration. The carbon absorption model of recycled concrete with recycled powder was optimized and validated by rapid carbonization tests. It is found that conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…As proposed by Yu et al [70], the value of p SCGP is 74.38 kg/t. Xiao et al [5] have pointed out that p Sand is 0.649 kg/t and p Cement is 757.60 kg/t. The value of p Water is considered as zero in this model, as the CO 2 emission from water is negligible [71,72].…”
Section: Co 2 Emissions Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…As proposed by Yu et al [70], the value of p SCGP is 74.38 kg/t. Xiao et al [5] have pointed out that p Sand is 0.649 kg/t and p Cement is 757.60 kg/t. The value of p Water is considered as zero in this model, as the CO 2 emission from water is negligible [71,72].…”
Section: Co 2 Emissions Analysismentioning
confidence: 99%
“…Researchers have confirmed that the grinding process contributes to increasing the surface area of RCP and exposes the non-carbonized part in the building demolition. The increase in the CO 2 absorption of eco-efficient mortar can largely offset the CO 2 emissions from grinding [5,73]. Therefore, stimulating the potential of solid waste to meet the basic requirements of general cementitious materials is an effective method to reduce carbon emissions by the cement industry.…”
Section: Co 2 Emissions Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…As was reported previously, more than 17, 123, 850 and 15,000 Mt of construction and demolition waste (C&D) is produced per annum in Australia, USA, Europe and China, 6,7 respectively, but only 10% of them are being recycled 7 . Replacing natural aggregates with RCAs not only prevents the over‐exploitation and depletion of non‐renewable natural resources, but also reduces the environmental influence of disposal of C&D waste in landfill 8,9 …”
Section: Introductionmentioning
confidence: 99%